DYNAMICS OF PHYSICAL QUALITIES OF CADETS DURING THE EDUCATIONAL TRAINING PROCESS (World Bulletin of Physical Education and Sports Science, 2026)
Physical training is a key component of cadet education, as it ensures the development of physical qualities and functional readiness necessary for effective performance of professional duties. Systematic physical training during the educational process is expected to promote positive adaptations of the cardiovascular and respiratory systems, as well as improve overall physical preparedness. However, objective assessment of the dynamics of these adaptations at different stages of education remains an important scientific task.
Keywords: Cadets; physical fitness; functional readiness; educational training process; physical qualities; cardiovascular adaptation; PWC